Optical communications rules of thumb - Miller, John Lester, 1959- (McGraw-Hill's AccessEngineering., 2003)
Annotation We are taking the unique rules of thumb format that drove the authors previous Photonics Rules of Thumb, and creating a new volume for the Optical telecommunications field. Rules of thumb are short-cuts, tricks, and methods that industry vets have developed through long years of trial and error. These books share such rules with less experienced readers, who find such information incredibly valuable.